Bifunctional WC‐Supported RuO2 Nanoparticles for Robust Water Splitting in Acidic Media - Sun, Shu‐Chao; Jiang, Hao; Chen, Zi‐Yao; Chen, Qing; Ma, Ming‐Yuan; Zhen, Liang; Song, Bo; Xu, Cheng‐Yan (Angewandte Chemie International Edition, 2022)
We report the strong catalyst–support interaction in WC‐supported RuO2 nanoparticles (RuO2‐WC NPs) anchored on carbon nanosheets with low loading of Ru (4.11 wt.%), which significantly promotes the oxygen evolution reaction activity with a η10 of 347 mV and a mass activity of 1430 A gRu−1, eight‐fold higher than that of commercial RuO2 (176 A gRu−1). Theoretical calculations demonstrate that the strong catalyst–support interaction between RuO2 and the WC support could optimize the surrounding electronic structure of Ru sites to reduce the reaction barrier. Considering the likewise excellent catalytic ability for hydrogen production, an acidic overall water splitting (OWS) electrolyzer with a good stability constructed by bifunctional RuO2‐WC NPs only requires a cell voltage of 1.66 V to afford 10 mA cm−2. The unique 0D/2D nanoarchitectures rationally combining a WC support with precious metal oxides provides a promising strategy to tradeoff the high catalytic activity and low cost for acidic OWS applications. Unique 0D/2D WC‐supported RuO2 nanoparticles anchored on carbon nanosheets with low loading of Ru (4.11 wt.%) were constructed as a bifunctional electrocatalyst, applying a cell voltage of 1.66 V to realize acidic overall water splitting (OWS) with excellent long‐term stability.